Hans Kelsen und die Rechtssoziologie: Auseinandersetzungen mit Hermann U. Kantorowicz, Eugen Ehrlich und Max Weber - Kelsen, Hans; Paulson, Stanley L.; Kantorowicz, Hermann (Scientia-Verl., 1992)
Betr. Max Weber S. 104 - 119